Lean six sigma and its effect on absorptive capacity, innovation performance and sustainable competitive advantage / Muraliraj Jagantheran - Muraliraj , Jagantheran (2019)
The very nature of businesses in the current epoch is at a state of hyper competition. As globalization and technology takes over the essence of every aspect, managing business requires a strategic approach. Quality management, which philosophy revolves around the principles of continuous improvement, is an approach that could harvest relevant strategies in accordance to business cycles. Lean Six Sigma is a process improvement methodology which falls under the umbrella of quality management, touted as the latest management philosophy of the 21st century by scholars and practitioners alike. Although the profundity of Lean Six Sigma is prevalent to a certain extent, there are still companies that are unsuccessful with the application of the philosophy, particularly failing to appropriate its functions. Correspondingly, gaps in scholarly literatures displayed the lack of clarity which justifies how Lean Six Sigma could bring about far reaching prospects in terms of innovation and sustainability in competitive advantage in firms that embrace it which are very much a current necessity. The purpose of this study is to explore the possibility of Lean Six Sigma functioning as a source of dynamic capability through the concept of absorptive capacity. The study intends to delineate the relationship between the idiosyncrasies of Lean Six Sigma and components of absorptive capacity, which exemplifies dynamic capabilities. These capabilities are ideal cornerstones which enable firms to realize far reaching performance outcomes such as innovation and sustenance of competitive advantage. Using a Partial Least Square based Structural Equation Modeling (PLS-SEM), this study ran a quantitative analysis to test the theoretical framework drawing on a sample of 125 manufacturing organizations in Peninsular Malaysia. From 19 hypotheses studied, 11 explained significant findings. The results of the analysis elucidated Lean’s Social Practice (LSP), Six Sigma’s Role Structure (RS) and Structured Improvement Procedure (SIP) positively influences Potential Absorptive Capacity (PACAP) which resembles an exploration trait for an organization. Meanwhile, LSP, RS and Focus on Metrics (FOM) positively influences Realized Absorptive Capacity (RACAP) which resembles an exploitation trait. However, Lean’s Technical Practice (LTP) was found to be non-significant towards both PACAP and RACAP. PACAP also positively influence RACAP and sustainable competitive advantage (SCA). Whereas RACAP positively predicts innovation performance (IP) which subsequently influences SCA. The analysis revealed Lean Six Sigma allows for exploration and exploitation activities alike through PACAP and RACAP respectively, leading to ambidextrous characteristics. These capabilities in turn influence IP and SCA in firms, justifying the path towards overarching performance outcomes through the application of Lean Six Sigma. Finally, the study outlines some of the limitations of the study and makes several managerial, theoretical and policy implication which firms and government institutions in Malaysia could capitalize from. Additionally, avenues for future research were also identified and recommended. In short, this study enlightened how Lean Six Sigma, or its idiosyncrasies could be maneuvered towards achieving far reaching outcomes such as innovation and sustainability in competitive advantage in organizations by empirically asserting its disposition as source of dynamic capability.